DNA damage in liver cells of the tilapia fish Oreochromis mossambicus larva induced by the insecticide cyantraniliprole at sublethal doses during chronic exposure. (January 2020) - Xu, Chengbin; Fan, Yongmei; Zhang, Xiaokai; Kong, Weihao; Miao, Weiguo; Li, Qing X.
Abstract: Cyantraniliprole can effectively control lepidopteran pests and has been used all over the world. In general, the risk of cyantraniliprole seems low for fish, but the toxicity selectivity among different fish species was not clear. Here the acute toxicity and chronic effects of cyantraniliprole to juvenile tilapia ( Oreochromis mossambicus ) were assessed. The results showed that 96 h LC50 of cyantraniliprole to tilapia was 38.0 mg/L. After exposed for 28 days, specific growth rates of the blank control, solution control, and the treatments of 0.037, 0.37 and 3.7 mg/L of cyantraniliprole were 1.14, 0.95, 0.93, 0.82 and 0.70% per day, respectively. The results of micronucleus experiment and single cell gel electrophoresis showed that cyantraniliprole damaged DNA in liver cells of tilapia larvae. Quantitative PCR results showed that cyantraniliprole could induce the up-regulation of Rpa 3 that is responsible for the DNA repair. The significantly down-regulation of Chk 2 gene was related to p53 pathway. It is therefore proposed that cyantraniliprole causes DNA damage in liver cells of tilapia and activates DNA damage and repair pathways. Highlights: Cyantraniliprole showed low acute toxicity to tilapia. Cyantraniliprole delayed the development and decreased the growth rate. Cyantraniliprole could damage DNA in liver cells of tilapia larvae. Cyantraniliprole induced up-regulation of Rpa 3 gene, but down-regulation of Chk2 gene.